Voltage regulators for next generation microprocessors - López, Toni; Elferich, Reinhold; Alarcón, Eduard; SpringerLink (Online service). (New York Springer, 2011)
Voltage Regulators for Next Generation Microprocessors by: Toni López Reinhold Elferich Eduard Alarcón This book deals with energy delivery challenges of the power processing unit of modern computer microprocessors. It describes in detail the consequences of current trends in miniaturization and clock frequency increase, upon the power delivery unit, referred to as voltage regulator. This is an invaluable reference for anybody needing to understand the key performance limitations and opportunities for improvement, from both a circuit and systems perspective, of state-of-the-art power solutions for next generation CPUs.-Provides a comprehensive survey of the state-of-the-art in energy delivery for the power processing unit of modern microprocessors; -Describes in detail key technological improvements required to fulfill the new load specifications; -Explains from both a circuit and systems perspective the key performance limitations and opportunities for improvement of state-of-the-art power solutions
Introduction -- Model level 0: Switching behavior of power MOSFETs -- Model level 1: Piecewise linear analytical switching model -- Model level 2: Power loss model -- Model level 3: Optimization -- Roadmap Targets -- Conclusion
Includes bibliographical references and index
Electronic reproduction
Keywords: Voltage regulators; Microprocessors